INVESTIGAÇÃO DE ATIVIDADE ANTICARCINOGÊNICA DE EUPHORBIA TITHYMALOIDES USANDO LINHAGENS DE DROSOPHILA MELANOGASTER - LIBERATO, Ana Luísa Barros; GOUVEIA, Juceli Gonzalez; FIGUEIREDO, Patrícia de Oliveira; GUTERRES, Zaira da Rosa; GARCEZ, Walmir Silva; SOARES, Luzinátia Ramos (ANAIS DO ENIC, 2025)
.